Challenges for educators in meeting the needs of students bridging into tertiary education : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Adult Education at Massey University - Morgan, Cecile Jane (Massey University, 2003)
Tertiary pre-entry programmes are designed to assist students in attaining an academic qualification that will allow entry into undergraduate study programmes. This study explores the challenges that educators encounter in meeting the needs of students bridging into tertiary education. It includes a review of programme purposes from historical, political and social viewpoints. It also describes the traditional and current profile of students accessing such programmes. The educator role within tertiary pre-entry programmes is outlined, interlinked with teaching and learning theory. Integral to the study is an exploration of the philosophical assumptions underpinning current teaching practice in relation to students, programmes and the future direction of tertiary pre-entry education. However, it is difficult to isolate an educator perspective from institutional and political perspectives. Hence this study addresses all these. The various perspectives all closely connect to create the learning environment that comprises current tertiary pre-entry programmes. The study identifies a number of tension areas between philosophical assumptions and practice that educators need to consider in meeting current student needs in their learning endeavours. These areas are: • The learning environment that students encounter • The people who interact in these environments • Future directions of tertiary pre-entry programmes. The study makes recommendations, from an educator's perspective, on what is required to lessen the tension and successfully meet the needs of the diverse student populace accessing tertiary pre-entry programmes.
Keywords: New Zealand -- Auckland; Developmental studies programs; College teaching -- New Zealand; Adult learning; Education, Higher